Unusual Behavior in Children- Foreign Object in Tooth: A Report of Two Cases - Mahesh, R (Ethiop J Health Sci, 2014)
BACKGROUND: The chance of discovering foreign object in a root canal is more commonly seen in children. Foreign objects may act as a potential source of infection, which may hinder the complete debridement of root canal. Although the main etiology being an accidental insertion, there are other possibilities such as self-injurious habits which should be ruled out. CASE DETAILS: The present article describes two case of foreign object in root canal, their possible etiology and management modalities. The first case reports a usual case of staple pin in root canal of primary teeth. The second case was a broken pin inside anterior permanent teeth. The cases reported highlight the need for proper diagnosis and early management. CONCLUSION: This case report highlights the need for proper understanding of the etiology in management of foreign body in root canal system.